Evidence for compromised data integrity in studies of liberal peri-operative inspired oxygen. - Myles, P. S.; Carlisle, J. B.; Scarr, B. (Anaesthesia, 2019)
In 2016 the World Health Organization recommended intra-operative ventilation with 80% inspired oxygen to reduce surgical site infection rates, based upon a meta-analysis of 15 randomised controlled trials, of which two were by Mario Schietroma's research group. Five trials by this group have been retracted for duplication, plagiarism, statistical error and lack of ethical approval. We analysed 40 papers by this group: 24 randomised controlled trials (5064 participants) and 16 observational studies (1847 patients). There was evidence that data integrity was compromised in 38 out of the 40 analysed papers. The distribution of baseline characteristics in randomised controlled trials was unlikely, p = 1.5 × 10-8 : continuous variables within trials were heterogeneous, p = 1.9 × 10-9 , and categorical variables were homogeneous, p = 8.5 × 10-20 . Effects of interventions varied less than expected between studies: for categorical variables, for instance postoperative wound infection, p < 1 × 10-7 , and for continuous variables, for instance HLA-DR concentration, p = 0.00001. Of 184 calculable p values, for baseline variables or results, 179 (98%) were incorrect, ranging from three orders of magnitude too small to 10 orders of magnitude too large. Twenty-one graphs occurred 81 times in 23 out of 40 papers. Liberal peri-operative oxygen did not reduce surgical site infection in a meta-analysis of 20 trials that excluded seven trials by Mario Schietroma and colleagues (odds ratio (95%CI) 0.89 (0.73-1.08); p = 0.23). An update by the World Health Organization has now excluded trials of liberal oxygen by Schietroma's group, four of which have not been retracted. We conclude that Mario Schietroma's work should not inform practice until investigated.